PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALLY (TAI) TERHADAP HASIL BELAJAR MATEMATIKA SISWA UPT SD NEGERI 7 WATANG SIDENRENG - S Pasinggi, Yonathan; Mukhlisa, Nurul; Halim, Suraeda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to find out the overview of students' mathematical learning outcomes and the influence of the application of Cooperative Learning Model Type Team Assisted Individually (TAI) on mathematics learning outcomes of UPT SD Negeri 7 Watang Sidenreng students. This study uses a type of pre-experimental design experiment research form one group pretest-posttest. The population in this study was all UPT SD Negeri 7 Watang Sidenreng students, while the sample consisted of 21 students in grade IV. Sampling in this study used the purposive sampling technique. The data collection technique used is multiple choice tests. The data analysis used is descriptive statistics and inferential statistics. The results of the data analysis showed that the results of the fourth grade students of UPT SD Negeri 7 Watang Sidenreng were processed with the average pretest score of 50.52 and the average posttest score of 82.47, which means that the students' learning results improved. Next, the hypothesis test was performed with the Paired Sample T-Test, which showed that H_a was accepted meaning that there was a difference in the mathematical learning outcomes of learning in the classroom of 4th grade UPT SD Negeri 7 Watang Sidenreng students before and after the application of the team assisted individually (TAI) type cooperative learning model. Therefore, it can be concluded that the application of the Cooperative Learning Model Type Team Assisted Individually (TAI) has an effect on the mathematics learning outcomes of 4th grade UPT SD Negeri 7 Watang Sidenreng students.